KEMENTERIAN RISET, TEKNOLOGI DAN PENDIDIKAN TINGGI - Wicita, Ade Triana; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This reseacrh describes about effort of indonesia to indonesian labours who get many problem in saudi arabia Starting with the factors driving the placement program of Indonesian Workers (TKI) in Saudi Arabia and then appears the case - the case of human rights violations suffered by the workers. Based on the fact that migrant workers are a national asset that bring in foreign exchange, the government's efforts to protect migrant workers must be increased. Based on the identification of cases affecting migrant workers in Saudi Arabia, the handling of the government to overcome the problem of placement and protection of migrant workers in Saudi Arabia may be said to have been unsuccessful. Identification of cases of late also will cause delays Indonesian government in dealing with the placement and protection of migrant workers. This study focused on the government's efforts in protecting workers.This research used the theory of diplomacy. As for the kind of diplomacy that used are bilateral diplomacy. Bilateral diplomacy is diplomacy carried out by between two countries. This research also used nation state analysis, this study applies qualitative research method with library.the data source are books, joournal, and internet.Finally, indonesian government’s action to protect the indonesian labours to be maximum as the effort that has been made are : do moraturium policy, bilateral diplomacy, appoint of retainer lawyer, assist in paying diyat also for the family of victims. Those effort can help theindonesian labours who get the punishment there, and it can be lighter for get a forgiveness from victim’s family or like paya fine and sorry.Keywords : Bilateral Diplomacy, effort, indonesian labours